Baseline values of Micronuclei and Comet Assay in the lizard Tupinambis merianae (Teiidae, Squamata) - Schaumburg, Laura Gisela (2012)
The Micronucleus test (MN) and Comet assay (CA) are currently the most widely used methods that allow the characterization of DNA damage induced by physical and chemical agents in wild species. The continuous expansion of the cultivated areas in Argentina, since the introduction of transgenic crops, mainly soy, in association with the increased use of pesticides, transformed deeply the natural environments where the lizard Tupinambis merianae occurs. Despite reptiles have shown to be excellent bioindicators of environmental contaminants, there is no record of genotoxicity studies in T. merianae. The aim of the present study was to adjust the MN test and CA protocols to be applied in erythrocytes of T. merianae, and determine the baseline values of DNA damage in this species. We used 20 adult lizards (10 males: 10 females) from Estación Zoológica Experimental “Granja La Esmeralda" (Santa Fe, Argentina). Peripheral blood samples were collected from all animals and the MN test and CA applied according to the protocols established for other reptilian species. We test critical parameters of CA protocol (cell density, unwinding and electrophoresis times) using increasing concentrations of H2O2 (10, 25 and 50 µM) as a known genotoxic agent to induce DNA damage. Based on this, we determined the most suitable conditions for the CA in this species: a cell density of 4 x 103 erythrocytes per slide, 10 min of unwinding and 15 min of electrophoresis at 0.90 V/cm approximately. The baseline frequency of micronuclei (BFMN= MN/1000 erythrocytescounted) determined for this species was 0.95 ± 0.27 and the basal damage index (BDI: calculated from 100 comet images classified in arbitrary units) = 103.85 ± 0.97. No differences were observed between sexes in the BFMN or BDI (p > 0.05), and no relation was found between baseline values and length or weight of the analyzed animals (p > 0.05). These results demonstrated the sensitivity of both biomarkers of genotoxicity to be applied in erythrocytes of this species, with baseline values comparable to those reported in other reptilian species. These results allow us to propose the tegu lizard for future in vivo studies to assess the genotoxicity of different agents, including those possibly affecting it in its natural geographic distribution.